Social policy versus social inequality: Just compromising injustices? - Venieris, Dimitris (The Greek Review of Social Research, 2011)
The paper provides a critical discussion of the controversial relationship between social policy and social inequality. This is primarily about investigating the principles of equality, liberty and justice which are central to an understanding of inequality and of social intervention. A social policy system is either radical or compromising. For those who prefer the radical option, the failure of social policy to substantially erode inequality in unquestionable. For those who choose the prevailing version of compromise, social policy may gain the support of the tax-paying middle classes and may offer a means of reconciling notions such as capitalism and social welfare. In short, there are two broad social policy options. First, a radical but optimistic version, where social policies are geared towards social change and vertical redistribution. Second, a compromise but survivingc one, where moderate social policies effect some degree of social mobility and horizontal redistribution. In any case, social policy has to develop a more sophisticated and complex analytical paradigm reconciling class and social movement theories and reconsidering the current complexities of social inequality. Postmodern social policy should incorporate social participation with welfare provisions and cultivate a social reform inspired by more commitment for less inequality.